2020
DOI: 10.3390/cells9020502
|View full text |Cite
|
Sign up to set email alerts
|

The Timing and Extent of Motor Neuron Vulnerability in ALS Correlates with Accumulation of Misfolded SOD1 Protein in the Cortex and in the Spinal Cord

Abstract: Understanding the cellular and molecular basis of selective vulnerability has been challenging, especially for motor neuron diseases. Developing drugs that improve the health of neurons that display selective vulnerability relies on in vivo cell-based models and quantitative readout measures that translate to patient outcome. We initially developed and characterized UCHL1-eGFP mice, in which motor neurons are labeled with eGFP that is stable and long-lasting. By crossing UCHL1-eGFP to amyotrophic lateral scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…However, would UCHL1 expression also help improve the health of CSMN that degenerate due to other causes? CSMN of hSOD1 G93A mice become vulnerable to degeneration very early in the disease and they display progressive degeneration with reduced soma size and apical dendrite degeneration [ 47 49 ]. To investigate whether overexpression of UCHL1 in CSMN that are diseased due to misfolded SOD1 would also improve their overall health, stability and cytoarchitectural integrity, we used the same AAV2 mediated gene delivery approach to deliver UCHL1 to CSMN that are diseased due to mutant SOD1 toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, would UCHL1 expression also help improve the health of CSMN that degenerate due to other causes? CSMN of hSOD1 G93A mice become vulnerable to degeneration very early in the disease and they display progressive degeneration with reduced soma size and apical dendrite degeneration [ 47 49 ]. To investigate whether overexpression of UCHL1 in CSMN that are diseased due to misfolded SOD1 would also improve their overall health, stability and cytoarchitectural integrity, we used the same AAV2 mediated gene delivery approach to deliver UCHL1 to CSMN that are diseased due to mutant SOD1 toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Since overexpression of the mutant form of SOD1 gene causes accumulation of misfolded SOD1 in hSOD1 G93A mouse model of ALS, and this is one of the major underlying causes of CSMN degeneration, we next investigated whether UCHL1 expression would also reduce the levels of misfolded SOD1 in CSMN by using the well characterized B8H10 monoclonal antibody that can detect misfolded SOD1 protein in a wide spectrum of SOD1 mutants and metal-depleted WT SOD1 protein, but not intact WT SOD1 [ 49 , 71 ]. CSMN of WT mice did not have misfolded SOD1, as expected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the present studies, we found a reduction in large corticospinal motor neurons in WT rats experiencing rTBI, similar to that seen in untreated SOD1 rats at the initiation of disease onset. While various cell types are affected in ALS, signs of corticospinal motor neuron degeneration have been shown to be early events in ALS patients and rodent models [ 2 , 5 , 34 ]. Importantly in our studies, atrophy of corticospinal motor neurons was not enough to induce a more severe neurodegenerative motor phenotype in WT rodents, which were followed out to over 52 weeks with persistent motor deficits but no signs of progressive phenotypic decline (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…While degeneration in both upper and lower motor neurons occurs in ALS patients and animal models, the exact origin of disease is unknown. Recent studies have found an early role for upper motor neurons in the brain in the initiation of disease [ 2 , 3 , 4 , 5 ]. However, despite convincing evidence of brain involvement in initiating motor circuitry breakdown, there is much to be understood regarding the role of the brain in ALS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, UCHL1-eGFP mice crossbred with SOD1 G93A mice demonstrate eGFP positive neurons are vulnerable in ALS disease progression [ 28 ]. Since their initial characterization, UCHL1-eGFP mice have been extensively used to study UMN degeneration in animal models of ALS, including alsin knockout (KO) and transgenic TDP-43 A315T mice [ 13 , 29 , 30 , 31 , 50 ], and therefore are an invaluable tool for uncovering the precise role of UMNs in ALS. While UCHL1-eGFP mice provide an appropriate model to label UMNs, eGFP and therefore UCHL1 are also expressed in neurons of the somatosensory cortex, striatum and spinal cord [ 28 ], which limits their utility to anatomical mapping studies, rather than functional studies.…”
Section: Transgenic Reporter Micementioning
confidence: 99%